Exploring the Permissibility of Mahar in the Form of Stocks in Islamic Law - Khoirul Anwar; Apriantoro, Muhamad Subhi (Ethica: International Journal of Humanities and Social Science Studies, 2023)
A dowry is a mandatory gift given by the prospective bridegroom to the prospective bride. In the general community, dowries are usually in the form of money, gold, and vehicles. Along with the development of the times, dowry is not only in the form of money, gold, and vehicles but also in the form of stocks, a new phenomenon among the general public. This study aims to enlighten the public about the law of giving dowry in the form of stocks. The results of this study indicate that giving a dowry in the form of stocks has many benefits for the bride and groom, so the law regarding giving a dowry is permissible.